ISL1 cardiovascular progenitor cells for cardiac repair after myocardial infarction - Oscar Bartulos; Zhen Wu Zhuang; Yan Huang; Nicole Mikush; Carol Suh; Alda Bregasi; Lin Wang; William Chang; Diane S. Krause; Lawrence H. Young; Jordan S. Pober; Yibing Qyang (JCI Insight, 2016)
Cardiovascular progenitor cells (CPCs) expressing the ISL1-LIM–homeodomain transcription factor contribute developmentally to cardiomyocytes in all 4 chambers of the heart. Here, we show that ISL1-CPCs can be applied to myocardial regeneration following injury. We used a rapid 3D methylcellulose approach to form murine and human ISL1-CPC spheroids that engrafted after myocardial infarction in murine hearts, where they differentiated into cardiomyocytes and endothelial cells, integrating into the myocardium and forming new blood vessels. ISL1-CPC spheroid–treated mice exhibited reduced infarct area and increased blood vessel formation compared with control animals. Moreover, left ventricular (LV) contractile function was significantly better in mice transplanted with ISL1-CPCs 4 weeks after injury than that in control animals. These results provide proof-of-concept of a cardiac repair strategy employing ISL1-CPCs that, based on our previous lineage-tracing studies, are committed to forming heart tissue, in combination with a robust methylcellulose spheroid–based delivery approach.